Solving a 112-bit prime elliptic curve discrete logarithm problem on game consoles using sloppy reduction. (1st January 2012) - Bos, Joppe W.; Kaihara, Marcelo E.; Kleinjung, Thorsten; Lenstra, Arjen K.; Montgomery, Peter L.
We describe a cell processor implementation of Pollard's rho method to solve discrete logarithms in groups of elliptic curves over prime fields. The implementation was used on a cluster of PlayStation 3 game consoles to set a new record. We present in detail the underlying single instruction multiple data modular arithmetic.